Exosomes derived from neural progenitor cells preserve photoreceptors during retinal degeneration by inactivating microglia. Issue 1 (21st April 2020) - Bian, Baishijiao; Zhao, Congjian; He, Xiangyu; Gong, Yu; Ren, Chunge; Ge, Lingling; Zeng, Yuxiao; Li, Qiyou; Chen, Min; Weng, Chuanhuang; He, Juncai; Fang, Yajie; et al.
ABSTRACT: Retinal degeneration (RD) is one of the most common causes of visual impairment and blindness and is characterized by progressive degeneration of photoreceptors. Transplantation of neural stem/progenitor cells (NPCs) is a promising treatment for RD, although the mechanisms underlying the efficacy remain unclear. Accumulated evidence supports the notion that paracrine effects of transplanted stem cells is likely the major approach to rescuing early degeneration, rather than cell replacement. NPC‐derived exosomes (NPC‐exos), a type of extracellular vesicles (EVs) released from NPCs, are thought to carry functional molecules to recipient cells and play therapeutic roles. In present study, we found that grafted human NPCs (hNPCs) secreted EVs and exosomes in the subretinal space (SRS) of RCS rats, an RD model. And direct administration of mouse neural progenitor cell‐derived exosomes (mNPC‐exos) delayed photoreceptor degeneration, preserved visual function, prevented thinning of the outer nuclear layer (ONL), and decreased apoptosis of photoreceptors in RCS rats. Mechanistically, mNPC‐exos were specifically internalized by retinal microglia and suppressed their activation in vitro and in vivo . RNA sequencing and miRNA profiling revealed a set of 17 miRNAs contained in mNPC‐exos that markedly inhibited inflammatory signal pathways by targeting TNF‐α, IL‐1β, and COX‐2 in activated microglia. The exosomes derived from hNPC (hNPC‐exos) contained similar miRNAs to mNPC‐exos that inhibited microglial activation. We demonstrated that NPC‐exos markedly suppressed microglial activation to protect photoreceptors from apoptosis, suggesting that NPC‐exos and their contents may be the mechanism of stem cell therapy for treating RD.